Riesgo reproductivo preconcepcional, drepanocitosis y coordinación entre los tres niveles de atención a la salud - Agramonte Llanes, Olga Margarita; Pérez Molina, Caridad; Tuttle Rodríguez, Ricardo (Mediciego, 2020)
In Cuba, the health of the mother and her child is part of one of the programs prioritized by the Ministry of Public Health: the Maternal and Child Care Program (PAMI)